Empirical research on early internationalization of firms in sufficiently-sized domestic market country - Saki Otomo; Shuichi Ishida; Mariko Yang-Yoshihara (Administrative Sciences, 2023)
Early internationalization and success in foreign markets play an important role in both a firm's growth and its impact on the global economy. We conducted a study on Japanese high-tech startups to investigate the factors that derive early internationalization in firms founded in countries with a large domestic market, despite the absence of strong incentives to operate overseas. Quantitative data were collected from 71 startups and analyzed with PLS-SEM (Partial least squares path modeling). Our result showed that the factors we extracted from the previous studies on the internationalization process in small-size markets would also apply in countries with large domestic markets. In addition, considerations and the types of technology, which we extracted from qualitative research, verified the effect. According to our mediator analysis, an entrepreneur's international orientation explains certain conditions related to a domestic market that affect a firms' decision to pursue early internationalization. Our study makes contributions at multiple levels, benefiting entrepreneurs who are considering overseas expansion as well as policymakers who aim to promote early internationalization efforts.
Keywords: 350; born global; entrepreneurship; innovation; innovative organization; internationalization; startups